O impacto e os benefícios da nova Lei de Licitações 14.133/2021 sob a perspectiva dos empresários: uma abordagem usando machine learning - Monte, Vinícius Freitas (Brasil, 2024)
The Law No. 14,133/2021 represents a significant advancement for public procurement in Brazil, aiming to modernize, streamline, and promote efficiency in the processes. This new legislation provides a more flexible and adaptable framework, aligned with international best practices, with the goal of improving the management of public resources and encouraging the participation of micro and small enterprises. This study aimed to understand the consequences of the implementation of the new Public Procurement Law No. 14,133 and its impacts and benefits for the business sector. A qualitative research strategy was employed, applying the semi-structured interview technique. The research subjects were entrepreneurs from the city of Manaus, active in various sectors working with Public Administration. The expected results include a detailed analysis of the entrepreneurs' perceptions of the changes brought by the new law, identifying the main challenges and opportunities. The research also aims to provide practical recommendations for companies to adapt to the new requirements and maximize the benefits of the legislation.